2020
DOI: 10.1002/etc.4718
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Improved Understanding of the Ingestion and Trophic Transfer of Microplastic Particles: Critical Review and Implications for Future Research

Abstract: Microplastic particles have been observed in the environment and routinely detected in the stomachs and intestines of aquatic organisms over the last 50 yr. In the present review, information on the ingestion of plastic debris of varying sizes is collated, including data for >800 species representing approximately 87 000 individual organisms, for which plastic debris and microplastic particles have been observed in approximately 17 500, or 20%. The average reported number of microplastic particles/individual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 173 publications
(254 reference statements)
9
73
0
1
Order By: Relevance
“… 8 11 Their ubiquity in aquatic systems and their small size has resulted in concerns regarding their effects on aquatic biota for which ingestion has been observed at all levels of biological organization. 12 14 …”
Section: Introductionmentioning
confidence: 99%
“… 8 11 Their ubiquity in aquatic systems and their small size has resulted in concerns regarding their effects on aquatic biota for which ingestion has been observed at all levels of biological organization. 12 14 …”
Section: Introductionmentioning
confidence: 99%
“…Finally, the widespread contamination of hundreds of species of wildlife across all trophic levels (Gall and Thompson, 2015), with evidence that plastics can be transported via trophic transfer (Provencher et al, 2019), demonstrates that organisms are also reservoirs and transporters of plastic pollution. Direct ingestion of large plastic debris (Gall and Thompson, 2015) and microplastics has been observed in hundreds of species and across many trophic levels (Gouin, 2020). Other routes of entry include uptake via the gills or indirect ingestion through the consumption of prey (Farrell and Nelson, 2013;Watts et al, 2014).…”
Section: The Fate Of Plastic In Our Oceanmentioning
confidence: 99%
“…Degradation processes facilitate the breakup of one piece of plastic into many smaller pieces that may eventually become micro-and nanoplastics (Song et al, 2017). Smaller-sized plastics have different fates in the water column (Kooi et al, 2017) and in an organism (Gouin, 2020). A recent study demonstrated that carbon from microplastics mineralized and utilized by microbes was in turn used by phytoplankton and zooplankton in their cell membrane fatty acids (Taipale et al, 2019).…”
Section: The Fate Of Plastic In Our Oceanmentioning
confidence: 99%
“…The ingestion of marine plastic debris (MPD) is a widespread and pervasive phenomenon globally (Cole, Lindeque, Halsband, & Galloway, 2011;Gall & Thompson, 2015;Gouin, 2020;Markic, Gaertner, Gaertner-Mazouni, & Koelmans, 2020), which has been documented in an increasing number of marine species, ranging from lower-trophic-consumers (e.g. gelatinous zooplankton ;Macali et al, 2018) to upper-trophic predators (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…cetaceans ;Lusher et al, 2018). Multispecies assessments have documented MPD ingestion in commercially valuable fish species and their prey (Gouin, 2020;Markic et al, 2020). Yet, despite some recent comparative studies (Forrest & Hindell, 2018;Markic et al, 2018;Thiel et al, 2018), understanding of how plastic contamination of commercial fish species differs across the Pacific Ocean is inhibited by a lack of data for many regions and archipelagos.…”
Section: Introductionmentioning
confidence: 99%